2021
DOI: 10.3390/pr9091504
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evaluation of Hydrotreated Vegetable Oils as Novel Feedstocks for Steam-Cracking Process

Abstract: Hydrotreated vegetable oils (HVOs) are currently a popular renewable energy source, frequently blended into a Diesel-fuel. In the paper, HVO potential as feedstock for the steam-cracking process was investigated, since HVOs promise high yields of monomers for producing green polymers and other chemicals. Prepared HVO samples of different oil sources were studied experimentally, using pyrolysis gas chromatography to estimate their product yields in the steam-cracking process and compare them to traditional feed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…These processes fall under the general umbrella of hydroprocessing technologies, which involve the removal of the double bonds and heteroatoms from vegetable oil in the presence of a catalyst and hydrogen atmosphere [32][33][34]. Since hydroprocessed vegetable oils (HVOs) are predominantly n-paraffins, steam cracking of HVO represents an opportunity to produce the molecular building blocks of the plastic industry [35,36]. Karaba et al demonstrated the suitability of HVO for the steam cracking process by obtaining large yields of ethylene (39.9-45.6 wt%), propylene (18.7-19.2 wt%) and C 4 hydrocarbons (15.2-18.2 wt%) from a micro pyrolysis reactor [36].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…These processes fall under the general umbrella of hydroprocessing technologies, which involve the removal of the double bonds and heteroatoms from vegetable oil in the presence of a catalyst and hydrogen atmosphere [32][33][34]. Since hydroprocessed vegetable oils (HVOs) are predominantly n-paraffins, steam cracking of HVO represents an opportunity to produce the molecular building blocks of the plastic industry [35,36]. Karaba et al demonstrated the suitability of HVO for the steam cracking process by obtaining large yields of ethylene (39.9-45.6 wt%), propylene (18.7-19.2 wt%) and C 4 hydrocarbons (15.2-18.2 wt%) from a micro pyrolysis reactor [36].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Since hydroprocessed vegetable oils (HVOs) are predominantly n-paraffins, steam cracking of HVO represents an opportunity to produce the molecular building blocks of the plastic industry [35,36]. Karaba et al demonstrated the suitability of HVO for the steam cracking process by obtaining large yields of ethylene (39.9-45.6 wt%), propylene (18.7-19.2 wt%) and C 4 hydrocarbons (15.2-18.2 wt%) from a micro pyrolysis reactor [36].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Therefore, the use of such crude biomass oils remain a longer-term possibility. Table 1 shows the typical composition of various bio-based feedctocks that can be used for co-processing in refineries [16][17][18][19][20][21][22][23][24][25][26].…”
Section: Feedstocks For Co-processingmentioning
confidence: 99%
“…The whole situation is even more complicated by the fact that C4 hydrocarbon fraction is not commonly processed by steam cracking alone, but in mixtures with heavier alkane materials with the aim to optimize the cracking capacity and to reduce the coke deposition [ 11 , 12 , 13 ]. Mutual interactions of hydrocarbons that are present in such a mixture are very essential in such situations and they are also generally important in relation to processing feedstocks that are based on renewable materials [ 14 ].…”
Section: Introductionmentioning
confidence: 99%